Gas sensor surface anti-interference coating and preparation method thereof
By preparing a nanocomposite coating on the surface of a gas sensor, the problem of poor anti-interference performance of the gas sensor was solved, and strong adsorption of interfering substances and high sensitivity detection of target gases were achieved.
Patent Information
- Application Number
- CN202511561194.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-29
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-10-29
AI Technical Summary
Existing gas sensors have poor anti-interference performance and are easily affected by interference such as ethanol and smoke, leading to false alarms or decreased sensitivity. Furthermore, traditional coating materials are prone to failure.
A composite coating composed of nano-silica, nano-titanium dioxide, nano-tin dioxide and palladium chloride substrate is formed by mixing, sintering and drying to form an anti-interference material coating, which enhances the adsorption capacity of interfering substances without affecting the transmission rate of detection gases such as methane.
It significantly improves the anti-interference capability of the gas sensor, reduces the response voltage of interfering substances, extends the service life of the coating, and maintains the detection sensitivity of the target gas.
Smart Images

Figure CN121022151A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of sensor coating, and particularly relates to a gas sensor surface anti-interference coating and a preparation method thereof. BACKGROUND
[0002] The main function of a gas sensor is to monitor the concentration of combustible or toxic gas in the environment in real time. Through chemical or physical reactions such as resistance change, current change, infrared absorption, etc., the gas concentration is converted into an electrical signal, and when the concentration exceeds the safety threshold, an alarm or linkage control is triggered to prevent accidents such as explosions and poisoning. Applied to the family: detect kitchen gas leakage to prevent explosions or poisoning. Applied to industry: monitor gas leakage of gas pipelines, storage tanks, and production workshops.
[0003] The existing gas sensor has poor anti-interference performance. Gas sensors such as methane and propane sensors are often interfered by ethanol, smoke, and oil smoke in practical applications, leading to false alarms or reduced sensitivity. In order to improve the anti-interference performance, existing gas sensors are wrapped with activated carbon and other materials to adsorb small-molecule organic compounds such as aldehydes and olefins in oil smoke, reducing chemical interference with the sensor. However, activated carbon is easily deactivated when exposed to air for a long time. The adsorption of activated carbon is mainly based on physical adsorption: intermolecular van der Waals forces, and a small amount of chemical adsorption: such as forming chemical bonds with some polar molecules, and its adsorption capacity depends on the "storage space" provided by the pore structure. However, this adsorption is reversible and limited: when the pores of activated carbon are filled with impurity molecules in the air, it can no longer adsorb new substances, i.e. "adsorption saturation"; the binding force of physical adsorption is weak, and changes in environmental conditions such as temperature and humidity can cause the desorption of adsorbed molecules, releasing pore space, but at the same time, it can also accelerate the adsorption of new impurities, shorten the effective life, and cause the adsorption capacity of the sensor to the interfering substances to decrease rapidly.
[0004] The most important thing for a sensor in use is to ensure its sensitivity. Although the skilled person in the art has tried to set a coating on the surface of the sensor, it is generally used for low-sensitivity materials, and the main purpose is: 1. Through the porous and high-surface-area structure of the coating to adsorb more gas molecules, improve the sensitivity of the sensor, but this application is not suitable for nanoscale materials; 2. Reduce the influence of specific environment on the gas sensor, such as moisture-proof, but at the same time, it will greatly reduce the sensitivity of the sensor. SUMMARY
[0005] In order to solve the above technical problems, the present application provides a gas sensor surface anti-interference coating and a preparation method thereof, which solves the problem of poor anti-interference performance of the current gas sensor material, and cannot meet the phenomenon of false alarm caused by the influence of interfering gas on the product.
[0006] In order to achieve the above technical purposes, the technical scheme provided by the present application is as follows: A gas sensor surface anti-interference coating, comprising the following materials by mass fraction: nanometer silicon dioxide 5.5-10.5 parts, nanometer titanium dioxide 3.5-5.6 parts, nanometer tin dioxide 10-15.5 parts, palladium chloride substrate 1-2 parts and distilled water.
[0007] Preferably, the following materials by mass fraction are included: nanometer silicon dioxide 8.3-9.7 parts, nanometer titanium dioxide 4.2-5.2 parts, nanometer tin dioxide 10.8-13.2 parts, 10% palladium chloride substrate 1-2 parts and distilled water.
[0008] Most preferably, the following materials by mass fraction are included: nanometer silicon dioxide 9.1 parts, nanometer titanium dioxide 4.6 parts, nanometer tin dioxide 11.8 parts, palladium chloride substrate 1.5 parts and distilled water.
[0009] A preparation method of a gas sensor surface anti-interference coating, comprising the following steps: S1: nanometer tin dioxide, nanometer silicon dioxide and nanometer titanium dioxide are mixed and ground.
[0010] S2: the mixed material of S1 is subjected to sintering treatment, the sintering temperature is 300-500 DEG C, and the time is 1-2 h.
[0011] S3: the nanometer composite material after sintering of S2 is mixed with a palladium chloride substrate chemical aqueous solution and a polar protic solvent, and is ground again.
[0012] S4: the nanometer composite material after mixing and grinding of S3 is subjected to drying treatment to remove the solvent, and a final gas sensor nanometer composite anti-interference material coating is formed.
[0013] Preferably, the tin dioxide in step S1 is tin dioxide prepared by chemical oxidation method or calcination method from metal tin with a purity of 99.999%.
[0014] Preferably, the sintering temperature in step S2 is 340-440 DEG C, the time is 2 h, and the drying temperature in step S4 is 60-100 DEG C.
[0015] Most preferably, the sintering temperature in step S2 is 380 DEG C, and the time is 2 h.
[0016] Most preferably, the drying temperature in step S4 is 80 DEG C.
[0017] Preferably, the palladium chloride substrate chemical aqueous solution in step S3 is a 10% palladium chloride substrate chemical aqueous solution, and the polar protic solvent is water or ethanol.
[0018] The present application has the following beneficial effects: The nanocomposite anti-interference material coating prepared by the present application has strong adsorption capacity for interference substances of the gas sensor, greatly reduces the penetration thereof, and does not affect the permeability of methane and other detection gases, so that the response voltage of the gas sensor to interference substances is significantly reduced, the anti-interference ability is improved, and the surface coating does not fail. The present application solves the problem that the anti-interference performance of the gas sensor material is poor and cannot meet the requirement of preventing false alarms caused by the influence of interference gases on the sensor. The nanocomposite anti-interference coating prepared by the present application is attached to the surface of the sensor without affecting the sensitivity of the sensor, which breaks the cognition in the field that the surface coating of the sensor must affect the sensitivity of the sensor. BRIEF DESCRIPTION OF DRAWINGS
[0019] Figure 1 Structure diagram of the anti-interference coating on the surface of the gas sensor prepared by the present application.
[0020] Figure 2 Diagram of the attachment state of the anti-interference coating on the surface of the gas sensor of the present application on the gas sensor. DETAILED DESCRIPTION
[0021] In order to make the technical purpose, technical scheme and technical effects of the present application more easily understood, further description will be made in combination with the drawings and specific embodiments.
[0022] The gas sensor without the anti-interference coating is used as a control, 3000 ppm of methane is used as the detection gas, and 3000 ppm of ethanol is used as the interference gas. The gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously injected into the transparent box. Timing starts after the injection of the gases, and the gases are pumped out at 15 seconds. The anti-interference performance and sensitivity of the gas sensor without the coating are shown in Table 1. The response voltage values of the detection gas methane and the interference gas ethanol are close, which is easy to cause false alarms.
[0023] Table 1 Anti-interference performance of the sensor without the coating Example 1
[0024] 1. An anti-interference coating on the surface of a gas sensor, comprising the following materials by mass: 5.5 g of nanosilica, 3.5 g of nanotitanium dioxide, 10.5 g of nanotin dioxide, 1 g of palladium chloride substrate, and 10 mL of distilled water.
[0025] 2. A preparation method of an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nanotin dioxide: pure metal tin with a purity of 99.999% is oxidized to tin dioxide by a chemical oxidation method or a calcination method.
[0026] (2) Mixed grinding: Nanometer silicon dioxide 5.5 g, nanometer titanium dioxide 3.5 g, nanometer tin dioxide 10.5 g are mixed well and ground by automatic grinding machine to ensure their uniform distribution.
[0027] (3) Sintering: The mixed material is sintered at a sintering temperature of 300°C for 1 h to ensure the crystallinity and density of the material.
[0028] (4) Mixed grinding with palladium chloride and trace amount of chemical solvent: The sintered nanometer composite material is mixed with 5 mL of 10% palladium chloride base chemical aqueous solution and 10 mL of distilled water, and is ground again; the palladium chloride may be partially dissociated in the solvent to form palladium ion catalyst, which can interact with the surface of tin dioxide to form doping or surface modification.
[0029] (5) Drying of the material: The nanometer composite material after mixed grinding is dried at 60°C to remove the solvent and form the final gas sensor nanometer composite anti-interference material coating.
[0030] 3. Anti-interference performance verification The nanometer composite anti-interference material coating prepared above is coated on a gas sensor, and then its anti-interference performance, sensitivity and adhesion forming ability are detected. 3000 ppm of methane is used as the gas to be detected, and 3000 ppm of ethanol is used as the interference gas. The gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously injected into the transparent box. The response voltage values of the methane to be detected and the ethanol interference gas are greater than those of the comparative example, and the difference is 1.31 V at the maximum response voltage, and no false alarm phenomenon occurs. Compared with the sensor without coating, the sensor coated with the coating prepared above also produces a greater response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gas. The coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches and clamp clamping without falling off and cracking phenomenon.
[0031] Table 2 Anti-interference performance and adhesion forming ability of the coating sensor coated with example 1 Example 2
[0032] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass fraction: nanometer silicon dioxide 6 g, nanometer titanium dioxide 3.5 g, nanometer tin dioxide 10.5 g, palladium chloride base 2 g and distilled water 15 mL.
[0033] 2. A method for preparing a surface anti-interference coating for a gas sensor, comprising the following steps: (1) Preparation of nano-tin dioxide: tin metal with a purity of 99.999% is oxidized to tin dioxide by a chemical oxidation method or a calcination method.
[0034] (2) Mixing and grinding: 6 g of nano-silicon dioxide, 3.5 g of nano-titanium dioxide, and 10.5 g of nano-tin dioxide are thoroughly mixed and ground by an automatic grinding machine to ensure uniform distribution.
[0035] (3) Sintering: the mixed material is subjected to sintering treatment at a sintering temperature of 320°C for 1.5 h to ensure the crystallinity and density of the material.
[0036] (4) Mixing and grinding with palladium chloride and a trace amount of chemical solvent: the sintered nano-composite material is mixed with 5 mL of a 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and is ground again; the palladium chloride may be partially dissociated in the solvent to form palladium ion catalysts, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0037] (5) Drying of the material: the nano-composite material after mixing and grinding is subjected to drying treatment at 65°C to remove the solvent and form the final gas sensor nano-composite anti-interference material coating.
[0038] 3. Anti-interference performance verification The nano-composite anti-interference material coating prepared above is coated on a gas sensor, and then its anti-interference performance, sensitivity, and adhesion forming ability are detected. With 3000 ppm of methane as the to-be-detected gas and 3000 ppm of ethanol as the interference gas, the gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously filled into the transparent box. The response voltage values of the to-be-detected gas methane and the interference gas ethanol are greatly different from those of the comparative example, and the difference is 1.29 V at the maximum response voltage, and no false alarm phenomenon occurs. Compared with no coating, the sensor coated with the coating prepared above also produces a large response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gases. The coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0039] Table 3 Anti-interference performance and adhesion forming ability of the sensor coated with the coating of Example 2 Example 3
[0040] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: Nano-silicon dioxide 6.5 g, nano-titanium dioxide 4.5 g, nano-tin dioxide 10.5 g, palladium chloride substrate 1 g and distilled water 10 mL.
[0041] 2. A method for preparing a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nano-tin dioxide: tin with a purity of 99.999% is oxidized to tin dioxide by a chemical oxidation method or a calcination method.
[0042] (2) Mixing and grinding: nano-silicon dioxide 5.5 g, nano-titanium dioxide 3.5 g, nano-tin dioxide 10.5 g are mixed thoroughly and ground by an automatic grinder to ensure uniform distribution.
[0043] (3) Sintering: the mixed materials are sintered at a temperature of 340°C for 2 h to ensure the crystallinity and density of the materials.
[0044] (4) Mixing and grinding with palladium chloride and a trace amount of chemical solvent: the sintered nano-composite material is mixed with 5 mL of a 10% palladium chloride substrate aqueous solution and 10 mL of distilled water, and is ground again; palladium chloride may partially dissociate in the solvent to form palladium ion catalysts, which can interact with the surface of tin dioxide to form doping or surface modification.
[0045] (5) Drying: the nano-composite material after mixing and grinding is dried at 65°C to remove the solvent and form the final gas sensor nano-composite anti-interference material coating.
[0046] 3. Anti-interference performance verification The nano-composite anti-interference material coating prepared above is coated on a gas sensor, and then its anti-interference performance, sensitivity and adhesion forming ability are detected. With 3000 ppm of methane as the to-be-detected gas and 3000 ppm of ethanol as the interference gas, the gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously filled into the transparent box. The response voltage values of the to-be-detected gas methane and the interference gas ethanol are detected. The difference between the response voltage values of the to-be-detected gas methane and the interference gas ethanol is larger than that of the comparative example, and the difference is 1.35 V at the maximum response voltage, and no false alarm phenomenon occurs. Compared with the sensor without coating, the sensor coated with the coating prepared above also produces a larger response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gases. The coating prepared above is attached to the surface of the sensor without cracks, sharp scratches and clamp clamping without falling off and cracking.
[0047] Table 4: Interference rejection performance and adhesion capability of coating of example 3 Example 4
[0048] 1. A gas sensor surface interference rejection coating comprising the following materials by mass: 7g of nano-silica, 4.5g of nano-titania, 11.5g of nano-tin dioxide, 2g of palladium chloride substrate and 15ml of distilled water.
[0049] 2. A method for preparing a gas sensor surface interference rejection coating comprising the following steps: (1) Preparation of nano-tin dioxide: tin metal with a purity of 99.999% is oxidized to tin dioxide by chemical oxidation or calcination.
[0050] (2) Mixing and grinding: 7g of nano-silica, 4.5g of nano-titania and 11.5g of nano-tin dioxide are thoroughly mixed and ground using an automatic grinding machine to ensure uniform distribution.
[0051] (3) Sintering: the mixed materials are sintered at a temperature of 360°C for 1 hour to ensure crystallinity and density of the materials.
[0052] (4) Mixing and grinding with palladium chloride and trace amounts of chemical solvent: the sintered nano-composite material is mixed with 5ml of a 10% palladium chloride substrate aqueous solution and 15ml of distilled water and ground again; the palladium chloride may partially dissociate in the solvent to form palladium ion catalysts, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0053] (5) Drying of the material: the nano-composite material after mixing and grinding is dried at 75°C to remove the solvent and form the final gas sensor nano-composite interference rejection material coating.
[0054] 3. Verification of interference rejection performance The nanocomposite anti-interference material coating prepared above is coated on a gas sensor, and then the anti-interference performance, sensitivity and adhesion forming ability of the gas sensor are detected. 3000 ppm of methane is used as the gas to be detected, and 3000 ppm of ethanol is used as the interference gas. The gas sensor is placed in a sealed transparent box, and the transparent box is filled with methane and ethanol gas at the same time. The time is started from the filling of the gas, and the gas is pumped out at 15 seconds. The anti-interference performance and sensitivity of the gas sensor coated with the coating are shown in Table 5: the difference between the response voltage values of the methane to be detected and the ethanol interference gas is larger than that of the comparative example, and the difference is 1.33 V at the maximum response voltage, and no false alarm phenomenon occurs; compared with no coating, the sensor coated with the coating prepared above also produces a larger response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gas; the coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches and clamp clamping without falling off and cracking phenomenon.
[0055] Table 5 Anti-interference performance and adhesion forming ability of the coating sensor coated with the coating of Example 4 Example 5
[0056] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: 7.5 g of nanosilica, 4.5 g of nanotitanium dioxide, 11.5 g of nanotin dioxide, 1 g of palladium chloride substrate and 10 mL of distilled water.
[0057] 2. A preparation method of a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nanotin dioxide: the purity of 99.999% of metal tin is oxidized to tin dioxide by chemical oxidation method or calcination method.
[0058] (2) Mixing and grinding: 7.5 g of nanosilica, 4.5 g of nanotitanium dioxide and 11.5 g of nanotin dioxide are mixed and ground with an automatic grinding machine to ensure their uniform distribution.
[0059] (3) Sintering: the mixed material is sintered at a sintering temperature of 380°C for 2 h to ensure the crystallinity and density of the material.
[0060] (4) Mixing and grinding with palladium chloride and trace amount of chemical solvent: the sintered nanocomposite material is mixed with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and is ground again; the palladium chloride may be partially dissociated in the solvent to form a palladium ion catalyst, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0061] (5) Drying the mixed material: drying the mixed and ground nanocomposite material at 80°C to remove the solvent and form the final nanocomposite anti-interference material coating for the gas sensor.
[0062] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was coated on the gas sensor, and its anti-interference performance, sensitivity, and adhesion forming ability were then detected. With 3000 ppm of methane as the gas to be detected and 3000 ppm of ethanol as the interference gas, the gas sensor was placed in a sealed transparent box, and methane and ethanol gases were simultaneously injected into the transparent box. The response voltage values of the methane to be detected and the ethanol interference gas were significantly different from those of the comparative example, with a difference of 1.40 V at the maximum response voltage, and no false alarm phenomenon occurred. Compared with the sensor without coating, the sensor coated with the coating prepared above also produced a larger response voltage at a detection time of 9-12 seconds, indicating that the coating did not affect the sensitivity of the sensor in detecting gases. The coating prepared above adhered to the surface of the sensor without large cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0063] Table 6 Anti-interference performance and adhesion forming ability of the coating sensor coated with Example 5 Example 6
[0064] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: 8 g of nanosilica, 5.2 g of nanotitanium dioxide, 11.5 g of nanotin dioxide, 2 g of palladium chloride substrate, and 15 mL of distilled water.
[0065] 2. A method for preparing a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nanotin dioxide: oxidizing pure tin with a purity of 99.999% to tin dioxide by chemical oxidation or calcination.
[0066] (2) Mixing and grinding: thoroughly mixing 8 g of nanosilica, 5.2 g of nanotitanium dioxide, and 11.5 g of nanotin dioxide, and grinding them with an automatic grinder to ensure uniform distribution.
[0067] (3) Sintering: sintering the mixed material at a sintering temperature of 400°C for 1 h to ensure the crystallinity and density of the material.
[0068] (4) Mixing and grinding with palladium chloride and trace amount of chemical solvent: mixing the sintered nanocomposite material with 5 mL of 10% palladium chloride base chemical aqueous solution and 15 mL of distilled water, and grinding again; the palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0069] (5) Drying the mixture: drying the mixed and ground nanocomposite material at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0070] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was coated on the gas sensor, and its anti-interference performance, sensitivity, and adhesion forming ability were detected. With 3000 ppm of methane as the gas to be detected and 3000 ppm of ethanol as the interference gas, the gas sensor was placed in a sealed transparent box, and methane and ethanol gases were simultaneously injected into the transparent box. The response voltage values of the methane to be detected and the ethanol interference gas were significantly different from those of the comparative example, with a difference of 1.37 V at the maximum response voltage, and no false alarm phenomenon occurred. Compared with the sensor without coating, the sensor coated with the coating prepared above also produced a larger response voltage at a detection time of 9-12 seconds, indicating that the coating did not affect the sensitivity of the sensor in detecting gases. The coating prepared above adhered to the surface of the sensor without large cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0071] Table 7 Anti-interference performance and adhesion forming ability of the coating sensor coated with Example 5 Example 7
[0072] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: 10 g of nanosilica, 3.5 g of nanotitanium dioxide, 13.5 g of nanotin dioxide, 2 g of palladium chloride base, and 15 mL of distilled water.
[0073] 2. A method for preparing a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nanotin dioxide: oxidizing pure metal tin with a purity of 99.999% to tin dioxide by chemical oxidation method or calcination method.
[0074] (2) Mixed grinding: 10 g of nano-silica, 3.5 g of nano-titania, and 13.5 g of nano-tin dioxide are mixed and ground by an automatic grinder to ensure their uniform distribution.
[0075] (3) Sintering: the mixed material is sintered at a temperature of 480°C for 1.5 h to ensure the crystallinity and density of the material.
[0076] (4) Mixed grinding with palladium chloride and trace chemical solvent: the sintered nano-composite material is mixed with 5 mL of a 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and is ground again; the palladium chloride may be partially dissociated in the solvent to form palladium ion catalysts, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0077] (5) Drying of the material: the nano-composite material after mixed grinding is dried at 75°C to remove the solvent, forming the final gas sensor nano-composite anti-interference material coating.
[0078] 3. Anti-interference performance verification The nano-composite anti-interference material coating prepared above is coated on a gas sensor, and its anti-interference performance, sensitivity, and adhesion forming ability are detected. With 3000 ppm of methane as the to-be-detected gas and 3000 ppm of ethanol as the interference gas, the gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously injected into the transparent box. The response voltage values of the to-be-detected gas methane and the interference gas ethanol are greater than those of the comparative example, and the difference is 1.44 V at the maximum response voltage, and no false alarm phenomenon occurs. Compared with the sensor without coating, the sensor coated with the coating prepared above also produces a greater response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gas. The coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0079] Table 8 Anti-interference performance and adhesion forming ability of the coating sensor coated with Example 7 Example 8
[0080] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: 10.5 g of nano-silica, 5.6 g of nano-titania, 15.5 g of nano-tin dioxide, 1 g of palladium chloride substrate, and 10 mL of distilled water.
[0081] 2. A method for preparing a surface anti-interference coating for a gas sensor, comprising the following steps: (1) Preparation of nano-tin dioxide: tin metal with a purity of 99.999% is oxidized to tin dioxide by a chemical oxidation method or a calcination method.
[0082] (2) Mixing and grinding: 10.5 g of nano-silicon dioxide, 5.6 g of nano-titanium dioxide, and 15.5 g of nano-tin dioxide are thoroughly mixed and ground by an automatic grinding machine to ensure uniform distribution.
[0083] (3) Sintering: the mixed material is subjected to sintering treatment at a sintering temperature of 500°C for 2 h to ensure the crystallinity and density of the material.
[0084] (4) Mixing and grinding with palladium chloride and a trace amount of chemical solvent: the sintered nano-composite material is mixed with 5 mL of a 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and is ground again; the palladium chloride may be partially dissociated in the solvent to form palladium ion catalysts, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0085] (5) Drying of the material: the nano-composite material after mixing and grinding is subjected to drying treatment at 80°C to remove the solvent and form the final gas sensor nano-composite anti-interference material coating.
[0086] 3. Anti-interference performance verification The nano-composite anti-interference material coating prepared above is coated on a gas sensor, and then its anti-interference performance, sensitivity, and adhesion forming ability are detected. With 3000 ppm of methane as the to-be-detected gas and 3000 ppm of ethanol as the interference gas, the gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously filled into the transparent box. The response voltage values of the to-be-detected gas methane and the interference gas ethanol are greatly different from those of the comparative example, and the difference is 1.42 V at the maximum response voltage, and no false alarm phenomenon occurs. Compared with no coating, the sensor coated with the coating prepared above also produces a large response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gases. The coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0087] Table 9 Anti-interference performance and adhesion forming ability of the coating sensor coated with Example 8 Example 9
[0088] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: Nano-silicon dioxide 8.5 g, nano-titanium dioxide 5.2 g, nano-tin dioxide 11.5 g, palladium chloride substrate 1 g, and distilled water 10 mL.
[0089] 2. A method for preparing a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nano-tin dioxide: tin with a purity of 99.999% is oxidized to tin dioxide by a chemical oxidation method or a calcination method.
[0090] (2) Mixing and grinding: nano-silicon dioxide 8.5 g, nano-titanium dioxide 5.2 g, and nano-tin dioxide 11.5 g are thoroughly mixed and ground with an automatic grinder to ensure uniform distribution.
[0091] (3) Sintering: the mixed materials are subjected to sintering treatment at a sintering temperature of 420°C for 1.5 h to ensure the crystallinity and density of the materials.
[0092] (4) Mixing and grinding with palladium chloride and a trace amount of chemical solvent: the sintered nano-composite material is mixed with 5 mL of a 10% palladium chloride substrate aqueous chemical solution and 10 mL of distilled water, and is ground again; the palladium chloride may partially dissociate in the solvent to form palladium ion catalysts, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0093] (5) Drying the material: the nano-composite material after mixing and grinding is subjected to drying treatment at 70°C to remove the solvent and form the final gas sensor nano-composite anti-interference material coating.
[0094] 3. Anti-interference performance verification The nano-composite anti-interference material coating prepared above is coated on a gas sensor, and then its anti-interference performance, sensitivity, and adhesion forming ability are detected. With 3000 ppm of methane as the gas to be detected and 3000 ppm of ethanol as the interference gas, the gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously injected into the transparent box. The response voltage values of the methane to be detected and the ethanol interference gas are significantly different from those of the comparative example, with a difference of 1.49 V at the maximum response voltage, and no false alarm phenomenon occurs. Compared with the sensor without coating, the sensor coated with the coating prepared above also produces a larger response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gases. The coating prepared above is attached to the surface of the sensor without cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0095] Table 10. Anti-interference performance and adhesion forming ability of coating sensor of Example 9 Example 10
[0096] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass fraction: 9 g of nano-silicon dioxide, 5.5 g of nano-titanium dioxide, 12.5 g of nano-tin dioxide, 2 g of palladium chloride substrate, and 15 mL of distilled water.
[0097] 2. A method for preparing a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nano-tin dioxide: 99.999% pure metal tin is oxidized to tin dioxide by chemical oxidation or calcination method.
[0098] (2) Mixing and grinding: 9 g of nano-silicon dioxide, 5.5 g of nano-titanium dioxide, and 12.5 g of nano-tin dioxide are thoroughly mixed and ground with an automatic grinding machine to ensure uniform distribution.
[0099] (3) Sintering: The mixed material is sintered at a temperature of 440°C for 2 hours to ensure the crystallinity and density of the material.
[0100] (4) Mixing and grinding with palladium chloride and trace chemical solvent: The sintered nano-composite material is mixed with 5 mL of 10% palladium chloride substrate aqueous solution and 15 mL of distilled water, and then ground again. Palladium chloride may partially dissociate in the solvent to form palladium ion catalysts, which can interact with the surface of tin dioxide to form doping or surface modification.
[0101] (5) Drying the material: The nano-composite material after mixing and grinding is dried at 60°C to remove the solvent and form the final gas sensor nano-composite anti-interference material coating.
[0102] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above is coated on a gas sensor, and then the anti-interference performance, sensitivity and adhesion forming ability of the gas sensor are detected. 3000 ppm of methane is used as the gas to be detected, and 3000 ppm of ethanol is used as the interference gas. The gas sensor is placed in a sealed transparent box, and the transparent box is filled with methane and ethanol gas at the same time. The time is started from the filling of the gas, and the gas is pumped out at 15 seconds. The anti-interference performance and sensitivity of the gas sensor coated with the coating are shown in Table 11. The difference between the response voltage values of the methane to be detected and the ethanol interference gas is larger than that of the comparative example. The difference is 1.46 V at the maximum response voltage, and no false alarm phenomenon occurs. Compared with the coating-free sensor, the sensor coated with the coating prepared above also produces a larger response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting the gas. The coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches and clamp clamping without falling off and cracking phenomenon.
[0103] Table 11 Anti-interference performance and adhesion forming ability of the coating sensor coated with the coating of Example 10 Example 11
[0104] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: 9.5 g of nanosilica, 5.5 g of nanotitanium dioxide, 12.5 g of nanotin dioxide, 1 g of palladium chloride substrate and 10 mL of distilled water.
[0105] 2. A preparation method of a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nanotin dioxide: The purity of 99.999% of metallic tin is oxidized to tin dioxide by chemical oxidation method or calcination method.
[0106] (2) Mixing and grinding: 9.5 g of nanosilica, 5.5 g of nanotitanium dioxide and 12.5 g of nanotin dioxide are mixed and ground with an automatic grinding machine to ensure their uniform distribution.
[0107] (3) Sintering: The mixed material is subjected to sintering treatment at a sintering temperature of 460°C for 1 h to ensure the crystallinity and density of the material.
[0108] (4) Mixing and grinding with palladium chloride and trace amount of chemical solvent: The sintered nanocomposite material is mixed with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and is ground again. Palladium chloride may be partially dissociated in the solvent to form palladium ion catalysts, which can interact with the surface of tin dioxide to form doping or surface modification.
[0109] (5) Drying the mixed material: drying the mixed and ground nanocomposite material at 70°C to remove the solvent and form the final nanocomposite anti-interference material coating for the gas sensor.
[0110] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was coated on the gas sensor, and its anti-interference performance, sensitivity, and adhesion forming ability were then detected. With 3000 ppm of methane as the gas to be detected and 3000 ppm of ethanol as the interference gas, the gas sensor was placed in a sealed transparent box, and methane and ethanol gases were simultaneously injected into the transparent box. The response voltage values of the methane to be detected and the ethanol interference gas were significantly different from those of the comparative example, with a difference of 1.54 V at the maximum response voltage, and no false alarm phenomenon occurred. Compared with the sensor without coating, the sensor coated with the coating prepared above also produced a larger response voltage at a detection time of 9-12 seconds, indicating that the coating did not affect the sensitivity of the sensor in detecting gases. The coating prepared above adhered to the surface of the sensor without large cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0111] Table 12 Anti-interference performance and adhesion forming ability of the coating sensor coated with Example 11 Example 12
[0112] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: 8.6 g of nanosilica, 4.1 g of nanotitanium dioxide, 11.5 g of nanotin dioxide, 1 g of palladium chloride substrate, and 10 mL of distilled water.
[0113] 2. A method for preparing a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nanotin dioxide: oxidizing pure tin with a purity of 99.999% to tin dioxide by chemical oxidation or calcination.
[0114] (2) Mixing and grinding: thoroughly mixing 8.6 g of nanosilica, 4.1 g of nanotitanium dioxide, and 11.5 g of nanotin dioxide, and grinding them with an automatic grinder to ensure uniform distribution.
[0115] (3) Sintering: sintering the mixed material at a sintering temperature of 380°C for 1.5 h to ensure the crystallinity and density of the material.
[0116] (4) Mixing and grinding with palladium chloride and trace amount of chemical solvent: mixing the sintered nanocomposite material with 5 mL of 10% palladium chloride base chemical aqueous solution and 10 mL of distilled water, and grinding again; the palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0117] (5) Drying the mixture: drying the mixed and ground nanocomposite material at 65°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0118] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was coated on the gas sensor, and its anti-interference performance, sensitivity, and adhesion forming ability were detected. With 3000 ppm of methane as the gas to be detected and 3000 ppm of ethanol as the interference gas, the gas sensor was placed in a sealed transparent box, and methane and ethanol gases were simultaneously injected into the transparent box. The response voltage values of the methane to be detected and the ethanol interference gas were significantly different from those of the comparative example, with a difference of 1.51 V at the maximum response voltage, and no false alarm phenomenon occurred. Compared with the sensor without coating, the sensor coated with the coating prepared above also produced a larger response voltage at a detection time of 9-12 seconds, indicating that the coating did not affect the sensitivity of the sensor in detecting gas. The coating prepared above adhered to the surface of the sensor without large cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0119] Table 13 Anti-interference performance and adhesion forming ability of the coating sensor coated with Example 12 Example 13
[0120] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: 8.9 g of nanosilica, 4.4 g of nanotitanium dioxide, 12.5 g of nanotin dioxide, 2 g of palladium chloride base, and 15 mL of distilled water.
[0121] 2. A method for preparing a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nanotin dioxide: oxidizing pure metal tin with a purity of 99.999% to tin dioxide by chemical oxidation or calcination.
[0122] (2) Mixed grinding: Nanometer silicon dioxide 8.9g, nanometer titanium dioxide 4.4g, nanometer tin dioxide 12.5g are mixed well and ground by automatic grinder to ensure their uniform distribution.
[0123] (3) Sintering: The mixed material is sintered at a temperature of 400°C for 2h to ensure the crystallinity and density of the material.
[0124] (4) Mixed grinding with palladium chloride and trace chemical solvent: The sintered nanometer composite material is mixed with 5mL of 10% palladium chloride base chemical aqueous solution and 15mL of distilled water, and then ground again. Palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the surface of tin dioxide to form doping or surface modification.
[0125] (5) Drying: The nanometer composite material after mixed grinding is dried at 70°C to remove the solvent and form the final gas sensor nanometer composite anti-interference material coating.
[0126] 3. Anti-interference performance verification The nanometer composite anti-interference material coating prepared above is coated on a gas sensor, and then its anti-interference performance, sensitivity and adhesion forming ability are detected. 3000ppm of methane is used as the gas to be detected, and 3000ppm of ethanol is used as the interference gas. The gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously injected into the transparent box. The response voltage values of the methane to be detected and the ethanol interference gas are larger than those of the comparative example, and the difference is 1.59V at the maximum response voltage, which does not cause false alarm. Compared with the coating-free sensor, the sensor coated with the coating prepared above also produces a larger response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gas. The coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches and clamp clamping without falling off and cracking.
[0127] Table 14 Anti-interference performance and adhesion forming ability of coating sensor coated with example 13 Example 14
[0128] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: Nanometer silicon dioxide 8g, nanometer titanium dioxide 3.5g, nanometer tin dioxide 10.5g, palladium chloride base 1g and distilled water 10mL.
[0129] 2. A method for preparing a surface anti-interference coating for a gas sensor, comprising the following steps: (1) Preparation of nano-tin dioxide: tin metal with a purity of 99.999% is oxidized to tin dioxide by a chemical oxidation method or a calcination method.
[0130] (2) Mixing and grinding: 8 g of nano-silicon dioxide, 3.5 g of nano-titanium dioxide, and 10.5 g of nano-tin dioxide are thoroughly mixed and ground by an automatic grinding machine to ensure uniform distribution.
[0131] (3) Sintering: the mixed material is subjected to sintering treatment at a sintering temperature of 340°C for 1 h to ensure the crystallinity and density of the material.
[0132] (4) Mixing and grinding with palladium chloride and a trace amount of chemical solvent: the sintered nano-composite material is mixed with 5 mL of a 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and is ground again; the palladium chloride may be partially dissociated in the solvent to form palladium ion catalysts, which can interact with the surface of the tin dioxide to form doping or surface modification.
[0133] (5) Drying of the material: the nano-composite material after mixing and grinding is subjected to drying treatment at 65°C to remove the solvent and form the final gas sensor nano-composite anti-interference material coating.
[0134] 3. Anti-interference performance verification The nano-composite anti-interference material coating prepared above is coated on a gas sensor, and then its anti-interference performance, sensitivity, and adhesion forming ability are detected. With 3000 ppm of methane as the to-be-detected gas and 3000 ppm of ethanol as the interference gas, the gas sensor is placed in a sealed transparent box, and methane and ethanol gases are simultaneously filled into the transparent box. The response voltage values of the to-be-detected gas methane and the interference gas ethanol are greatly different from those of the comparative example, and the difference is 1.28 V at the maximum response voltage, and no false alarm phenomenon occurs. Compared with no coating, the sensor coated with the coating prepared above also produces a large response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting gases. The coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches, and clamp clamping without falling off and cracking.
[0135] Table 15 Anti-interference performance and adhesion forming ability of the coating sensor coated with Example 14 Example 15
[0136] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 8.3g of nano-silica, 3.8g of nano-titanium dioxide, 15.5g of nano-tin dioxide, 2g of palladium chloride substrate and 15mL of distilled water.
[0137] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0138] (2) Mixing and grinding: Mix 8.3g of nano silicon dioxide, 3.8g of nano titanium dioxide and 15.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0139] (3) Sintering: The mixed materials are sintered at a temperature of 360°C for 1 hour to ensure the crystallinity and density of the materials.
[0140] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0141] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 60°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0142] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 16: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.25V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0143] Table 16 Anti-interference performance and adhesion forming ability of coating sensor of Example 15 Example 16
[0144] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass fraction: 8 g of nano-silicon dioxide, 4.1 g of nano-titanium dioxide, 11 g of nano-tin dioxide, 1.5 g of palladium chloride substrate, and 10 mL of distilled water.
[0145] 2. A method for preparing a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nano-tin dioxide: 99.999% pure metal tin is oxidized to tin dioxide by chemical oxidation or calcination method.
[0146] (2) Mixing and grinding: 8 g of nano-silicon dioxide, 4.1 g of nano-titanium dioxide, and 11 g of nano-tin dioxide are thoroughly mixed and ground with an automatic grinding machine to ensure uniform distribution.
[0147] (3) Sintering: The mixed material is sintered at a temperature of 400°C for 1.5 hours to ensure the crystallinity and density of the material.
[0148] (4) Mixing and grinding with palladium chloride and trace chemical solvent: The sintered nano-composite material is mixed with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and then ground again. Palladium chloride may partially dissociate in the solvent to form palladium ion catalysts, which can interact with the surface of tin dioxide to form doping or surface modification.
[0149] (5) Drying the material: The nano-composite material after mixing and grinding is dried at 65°C to remove the solvent and form the final gas sensor nano-composite anti-interference material coating.
[0150] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above is coated on a gas sensor, and then the anti-interference performance, sensitivity and adhesion forming ability of the gas sensor are detected. 3000 ppm of methane is used as the gas to be detected, and 3000 ppm of ethanol is used as the interference gas. The gas sensor is placed in a sealed transparent box, and the transparent box is filled with methane and ethanol gas at the same time. The time is started from the filling of the gas, and the gas is pumped out at 15 seconds. The anti-interference performance and sensitivity of the gas sensor coated with the coating are shown in Table 17. The difference between the response voltage values of the methane to be detected and the ethanol interference gas is larger than that of the comparative example, and the difference is 1.32 V at the maximum response voltage, which does not cause false alarm. Compared with the uncoated sensor, the sensor coated with the coating prepared above also produces a larger response voltage at a detection time of 9-12 seconds, indicating that the coating does not affect the sensitivity of the sensor in detecting the gas. The coating prepared above is attached to the surface of the sensor without large cracks, sharp scratches and clamp clamping without falling off and cracking.
[0151] Table 17 Anti-interference performance and adhesion forming ability of the coating sensor coated with the coating of Example 16 Example 17
[0152] 1. A gas sensor surface anti-interference coating, comprising the following materials by mass: 9.5 g of nanosilica, 5 g of nanotitanium dioxide, 14.5 g of nanotin dioxide, 2 g of palladium chloride substrate and 15 mL of distilled water.
[0153] 2. A preparation method of a gas sensor surface anti-interference coating, comprising the following steps: (1) Preparation of nanotin dioxide: The purity of 99.999% of metallic tin is oxidized to tin dioxide by chemical oxidation method or calcination method.
[0154] (2) Mixing and grinding: 9.5 g of nanosilica, 5 g of nanotitanium dioxide and 14.5 g of nanotin dioxide are mixed and ground with an automatic grinding machine to ensure their uniform distribution.
[0155] (3) Sintering: The mixed material is sintered at a sintering temperature of 440°C for 2 h to ensure the crystallinity and density of the material.
[0156] (4) Mixing and grinding with palladium chloride and trace amount of chemical solvent: The sintered nanocomposite material is mixed with 5 mL of 10% palladium chloride substrate aqueous solution and 15 mL of distilled water, and then ground again. Palladium chloride may be partially dissociated in the solvent to form palladium ion catalysts, which can interact with the surface of tin dioxide to form doping or surface modification.
[0157] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0158] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 18: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.29V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0159] Table 18 shows the anti-interference performance and adhesion molding capability of the coating sensor in Example 17. Example 18
[0160] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 9.8g of nano-silica, 5.3g of nano-titanium dioxide, 15.5g of nano-tin dioxide, 1g of palladium chloride substrate and 10mL of distilled water.
[0161] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0162] (2) Mixing and grinding: Mix 9.8g of nano silicon dioxide, 5.3g of nano titanium dioxide and 15.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0163] (3) Sintering: The mixed materials are sintered at a temperature of 460℃ for 1 hour to ensure the crystallinity and density of the materials.
[0164] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0165] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 85°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0166] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 19: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.36V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0167] Table 19 shows the anti-interference performance and adhesion molding capability of the coating sensor in Example 18. Example 19
[0168] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 4.1g of nano-silica, 5.6g of nano-titanium dioxide, 15.5g of nano-tin dioxide, 1.5g of palladium chloride substrate and 15mL of distilled water.
[0169] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0170] (2) Mixing and grinding: Mix 4.1g of nano silicon dioxide, 5.6g of nano titanium dioxide and 15.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0171] (3) Sintering: The mixed materials are sintered at a temperature of 340℃ for 1.5h to ensure the crystallinity and density of the materials.
[0172] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0173] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 90°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0174] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 20: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.33V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0175] Table 20 shows the anti-interference performance and adhesion molding capability of the coating sensor in Example 19. Example 20
[0176] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 7.2g of nano-silica, 3.5g of nano-titanium dioxide, 10g of nano-tin dioxide, 2g of palladium chloride substrate and 10mL of distilled water.
[0177] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0178] (2) Mixing and grinding: Mix 7.2g of nano silicon dioxide, 3.5g of nano titanium dioxide and 10g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0179] (3) Sintering: The mixed materials are sintered at a temperature of 360°C for 2 hours to ensure the crystallinity and density of the materials.
[0180] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0181] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 95°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0182] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 21: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.40V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after scratching with sharp objects or clamping.
[0183] Table 21. Anti-interference performance and adhesion / forming ability of the coated sensor in Example 20. Example 21
[0184] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 7.6g of nano-silica, 3.8g of nano-titanium dioxide, 10.5g of nano-tin dioxide, 1g of palladium chloride substrate and 15mL of distilled water.
[0185] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0186] (2) Mixing and grinding: Mix 7.6g of nano-silica, 3.8g of nano-titanium dioxide and 10.5g of nano-tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0187] (3) Sintering: The mixed materials are sintered at a temperature of 380℃ for 1 hour to ensure the crystallinity and density of the materials.
[0188] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0189] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 100°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0190] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 22: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.38V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0191] Table 22 Anti-interference performance and adhesion / forming ability of the coating sensor in Example 21 Example 22
[0192] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 9.2g of nano-silica, 4.7g of nano-titanium dioxide, 13.5g of nano-tin dioxide, 1g of palladium chloride substrate and 10mL of distilled water.
[0193] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0194] (2) Mixing and grinding: Mix 9.2g of nano silicon dioxide, 4.7g of nano titanium dioxide and 13.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0195] (3) Sintering: The mixed materials are sintered at a temperature of 420°C for 1 hour to ensure the crystallinity and density of the materials.
[0196] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0197] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 75°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0198] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 23: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.45V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0199] Table 23 Anti-interference performance and adhesion / forming ability of the coating sensor in Example 22 Example 23
[0200] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 9.2g of nano-silica, 5g of nano-titanium dioxide, 12.5g of nano-tin dioxide, 1.5g of palladium chloride substrate and 15mL of distilled water.
[0201] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0202] (2) Mixing and grinding: Mix 9.2g of nano silicon dioxide, 5g of nano titanium dioxide and 12.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0203] (3) Sintering: The mixed materials are sintered at a temperature of 460℃ for 1.5h to ensure the crystallinity and density of the materials.
[0204] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0205] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0206] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 24: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.43V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0207] Table 24. Anti-interference performance and adhesion / forming ability of the coating sensor in Example 23. Example 24
[0208] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 8.8g of nano-silica, 4.7g of nano-titanium dioxide, 12g of nano-tin dioxide, 1g of palladium chloride substrate and 10mL of distilled water.
[0209] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0210] (2) Mixing and grinding: Mix 8.8g of nano silicon dioxide, 4.7g of nano titanium dioxide and 12g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0211] (3) Sintering: The mixed materials are sintered at a temperature of 440℃ for 1 hour to ensure the crystallinity and density of the materials.
[0212] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0213] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 75°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0214] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 25: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.50V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0215] Table 25. Anti-interference performance and adhesion / forming ability of the coated sensor in Example 24. Example 25
[0216] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 9.6g of nano-silica, 5.3g of nano-titanium dioxide, 13g of nano-tin dioxide, 2g of palladium chloride substrate and 10mL of distilled water.
[0217] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0218] (2) Mixing and grinding: Mix 9.6g of nano silicon dioxide, 5.3g of nano titanium dioxide and 13g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0219] (3) Sintering: The mixed materials are sintered at a temperature of 380℃ for 2 hours to ensure the crystallinity and density of the materials.
[0220] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0221] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 85°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0222] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box, and methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 26: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.47V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0223] Table 26 shows the anti-interference performance and adhesion molding capability of the coated sensor in Example 25. Example 26
[0224] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 8.4g of nano-silica, 4.4g of nano-titanium dioxide, 11.5g of nano-tin dioxide, 2g of palladium chloride substrate and 15mL of distilled water.
[0225] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0226] (2) Mixing and grinding: Mix 8.4g of nano silicon dioxide, 4.4g of nano titanium dioxide and 11.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0227] (3) Sintering: The mixed materials are sintered at a temperature of 420°C for 2 hours to ensure the crystallinity and density of the materials.
[0228] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0229] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 75°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0230] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 27: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.55V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0231] Table 27 shows the anti-interference performance and adhesion molding capability of the coating sensor in Example 26. Example 27
[0232] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 10g of nano-silica, 5.6g of nano-titanium dioxide, 13.5g of nano-tin dioxide, 1g of palladium chloride substrate and 15mL of distilled water.
[0233] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0234] (2) Mixing and grinding: Mix 10g of nano silicon dioxide, 5.6g of nano titanium dioxide and 13.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0235] (3) Sintering: The mixed materials are sintered at a temperature of 400℃ for 1 hour to ensure the crystallinity and density of the materials.
[0236] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0237] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 90°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0238] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 28: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.25V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0239] Table 28 shows the anti-interference performance and adhesion molding capability of the coating sensor in Example 27. Example 28
[0240] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 10.4g of nano-silica, 3.8g of nano-titanium dioxide, 14g of nano-tin dioxide, 1.5g of palladium chloride substrate and 10mL of distilled water.
[0241] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0242] (2) Mixing and grinding: Mix 10.4g of nano silicon dioxide, 3.8g of nano titanium dioxide and 14g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0243] (3) Sintering: The mixed materials are sintered at a temperature of 420°C for 1.5 hours to ensure the crystallinity and density of the materials.
[0244] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0245] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 65°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0246] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 29: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.22V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0247] Table 29 shows the anti-interference performance and adhesion molding capability of the coating sensor in Example 28. Example 29
[0248] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 10.5g of nano-silica, 3.5g of nano-titanium dioxide, 14.5g of nano-tin dioxide, 2g of palladium chloride substrate, and 15mL of distilled water.
[0249] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0250] (2) Mixing and grinding: Mix 10.5g of nano silicon dioxide, 3.5g of nano titanium dioxide and 14.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0251] (3) Sintering: The mixed materials are sintered at a temperature of 440℃ for 2 hours to ensure the crystallinity and density of the materials.
[0252] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0253] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 70°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0254] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 30: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.41V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0255] Table 30 shows the anti-interference performance and adhesion molding capability of the coated sensor in Example 29. Example 30
[0256] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 10.5g of nano-silica, 4.5g of nano-titanium dioxide, 15g of nano-tin dioxide, 1g of palladium chloride substrate, and 15mL of distilled water.
[0257] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0258] (2) Mixing and grinding: Mix 10.5g of nano-silica, 4.5g of nano-titanium dioxide and 15g of nano-tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0259] (3) Sintering: The mixed materials are sintered at a temperature of 460℃ for 1 hour to ensure the crystallinity and density of the materials.
[0260] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0261] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 75°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0262] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 31: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.28V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0263] Table 31. Anti-interference performance and adhesion molding capability of the coated sensor in Example 30. Example 31
[0264] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 10.5g of nano-silica, 5.5g of nano-titanium dioxide, 15g of nano-tin dioxide, 1.5g of palladium chloride substrate and 15mL of distilled water.
[0265] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0266] (2) Mixing and grinding: 10.5g of nano silicon dioxide, 5.5g of nano titanium dioxide and 15g of nano tin dioxide (3) Sintering: Sinter the mixed materials at a temperature of 500℃ for 2 hours to ensure the crystallinity and density of the materials.
[0267] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0268] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0269] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 32: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.26V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without large cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0270] Table 32 Anti-interference performance and adhesion / forming ability of the coating sensor in Example 31 Example 32
[0271] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 8.3g of nano-silica, 4.2g of nano-titanium dioxide, 10.8g of nano-tin dioxide, 2g of palladium chloride substrate and 10mL of distilled water.
[0272] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0273] (2) Mixing and grinding: Mix 8.3g of nano silicon dioxide, 4.2g of nano titanium dioxide and 10.8g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0274] (3) Sintering: The mixed materials are sintered at a temperature of 340℃ for 1 hour to ensure the crystallinity and density of the materials.
[0275] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0276] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0277] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 33: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.67V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface with almost no cracks, and showed no peeling or cracking after scratching with sharp objects or clamping.
[0278] Table 33. Anti-interference performance and adhesion molding capability of the coated sensor in Example 32. Example 33
[0279] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 8.6g of nano-silica, 4.4g of nano-titanium dioxide, 11.3g of nano-tin dioxide, 1g of palladium chloride substrate and 15mL of distilled water.
[0280] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0281] (2) Mixing and grinding: Mix 8.6g of nano silicon dioxide, 4.4g of nano titanium dioxide and 11.3g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0282] (3) Sintering: The mixed materials are sintered at a temperature of 360°C for 1.5 hours to ensure the crystallinity and density of the materials.
[0283] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0284] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 90°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0285] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 34: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.64V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface with almost no cracks, and showed no peeling or cracking after scratching with sharp objects or clamping.
[0286] Table 34. Anti-interference performance and adhesion molding capability of the coating sensor in Example 33. Example 34
[0287] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 9.1g of nano-silica, 4.6g of nano-titanium dioxide, 11.8g of nano-tin dioxide, 1.5g of palladium chloride substrate and 10mL of distilled water.
[0288] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0289] (2) Mixing and grinding: Mix 9.1g of nano silicon dioxide, 4.6g of nano titanium dioxide and 11.8g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0290] (3) Sintering: The mixed materials are sintered at a temperature of 380℃ for 2 hours to ensure the crystallinity and density of the materials.
[0291] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0292] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0293] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 35: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.77V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface without cracks, and showed no peeling or cracking after being scratched by sharp objects or clamped.
[0294] Table 35. Anti-interference performance and adhesion / forming ability of the coating sensor in Example 34. Example 35
[0295] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 9.35g of nano-silica, 4.8g of nano-titanium dioxide, 12.3g of nano-tin dioxide, 2g of palladium chloride substrate, and 15mL of distilled water.
[0296] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0297] (2) Mixing and grinding: Mix 9.35g of nano silicon dioxide, 4.8g of nano titanium dioxide and 12.3g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0298] (3) Sintering: The mixed materials are sintered at a temperature of 400℃ for 1 hour to ensure the crystallinity and density of the materials.
[0299] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0300] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 85°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0301] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 36: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.69V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface with almost no cracks, and showed no peeling or cracking after scratching with sharp objects or clamping.
[0302] Table 36. Anti-interference performance and adhesion / forming ability of the coating sensor in Example 35. Example 36
[0303] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 9.5g of nano-silica, 5g of nano-titanium dioxide, 12.8g of nano-tin dioxide, 1g of palladium chloride substrate and 10mL of distilled water.
[0304] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0305] (2) Mixing and grinding: Mix 9.5g of nano silicon dioxide, 5g of nano titanium dioxide and 12.8g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0306] (3) Sintering: The mixed materials are sintered at a temperature of 440℃ for 1.5h to ensure the crystallinity and density of the materials.
[0307] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0308] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 90°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0309] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 37: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.72V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating adhered to the sensor surface with almost no cracks, and showed no peeling or cracking after scratching with sharp objects or clamping.
[0310] Table 37. Anti-interference performance and adhesion molding capability of the coated sensor in Example 36. Example 37
[0311] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 9.7g of nano-silica, 5.2g of nano-titanium dioxide, 13.2g of nano-tin dioxide, 1.5g of palladium chloride substrate and 15mL of distilled water.
[0312] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0313] (2) Mixing and grinding: Mix 9.7g of nano silicon dioxide, 5.2g of nano titanium dioxide and 13.2g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0314] (3) Sintering: The mixed materials are sintered at a temperature of 460℃ for 2 hours to ensure the crystallinity and density of the materials.
[0315] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0316] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 100°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0317] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion formation ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 38: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 1.74V at the maximum response voltage, indicating no false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating showed large cracks on the sensor surface, and peeling and cracking occurred when scratched by sharp objects or clamped, indicating insufficient adhesion formation ability.
[0318] Table 38 shows the anti-interference performance and adhesion molding capability of the coating sensor in Example 37. Example 38
[0319] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 5.2g of nano-silica, 3.3g of nano-titanium dioxide, 9.5g of nano-tin dioxide, 1g of palladium chloride substrate and 10mL of distilled water.
[0320] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0321] (2) Mixing and grinding: Mix 5.2g of nano silicon dioxide, 3.3g of nano titanium dioxide and 9.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0322] (3) Sintering: The mixed materials are sintered at a temperature of 400℃ for 1.5h to ensure the crystallinity and density of the materials.
[0323] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0324] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0325] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the box, and timing began after injection. The gas was then evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 39. The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 0.70V at the maximum response voltage, which could lead to false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating showed large cracks on the sensor surface, and detachment and cracking occurred due to scratches from sharp objects and clamping.
[0326] Table 39 shows the anti-interference performance and adhesion molding capability of the coating sensor in Example 38. Example 39
[0327] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 10.8g of nano-silica, 5.9g of nano-titanium dioxide, 16g of nano-tin dioxide, 2g of palladium chloride substrate, and 15mL of distilled water.
[0328] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0329] (2) Mixing and grinding: Mix 10.8g of nano silicon dioxide, 5.9g of nano titanium dioxide and 16g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0330] (3) Sintering: The mixed materials are sintered at a temperature of 400℃ for 1.5h to ensure the crystallinity and density of the materials.
[0331] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 15 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0332] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0333] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box, and methane and ethanol gases were simultaneously injected into the box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 40: The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 0.68V at the maximum response voltage, which could lead to false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. The prepared coating showed large cracks on the sensor surface, and peeling and cracking occurred when scratched by sharp objects or clamped.
[0334] Table 40 shows the anti-interference performance and adhesion molding capability of the coated sensor in Example 39. Example 40
[0335] 1. An anti-interference coating for the surface of a gas sensor, comprising the following materials in parts by weight: 5.2g of nano-silica, 4.5g of nano-titanium dioxide, 11.5g of nano-tin dioxide, 1.5g of palladium chloride substrate and 10mL of distilled water.
[0336] 2. A method for preparing an anti-interference coating on the surface of a gas sensor, comprising the following steps: (1) Preparation of nano tin dioxide: 99.999% pure metallic tin is oxidized into tin dioxide by chemical oxidation or calcination.
[0337] (2) Mixing and grinding: Mix 5.2g of nano silicon dioxide, 4.5g of nano titanium dioxide and 11.5g of nano tin dioxide thoroughly and grind them with an automatic grinder to ensure that they are evenly distributed.
[0338] (3) Sintering: The mixed materials are sintered at a temperature of 400℃ for 1.5h to ensure the crystallinity and density of the materials.
[0339] (4) Mix and grind with palladium chloride and trace chemical solvent: Mix the sintered nanocomposite material with 5 mL of 10% palladium chloride substrate chemical aqueous solution and 10 mL of distilled water, and grind again; palladium chloride may partially dissociate in the solvent to form palladium ion catalyst, which can interact with the tin dioxide surface to form doping or surface modification.
[0340] (5) Drying and forming materials: The mixed and ground nanocomposite material is dried at 80°C to remove the solvent and form the final gas sensor nanocomposite anti-interference material coating.
[0341] 3. Anti-interference performance verification The nanocomposite anti-interference material coating prepared above was applied to a gas sensor, and its anti-interference performance, sensitivity, and adhesion and molding ability were then tested. Using 3000 ppm methane as the target gas and 3000 ppm ethanol as the interfering gas, the gas sensor was placed in a sealed transparent box. Methane and ethanol gases were simultaneously injected into the transparent box. Timing began after gas injection, and the gas was evacuated after 15 seconds. The anti-interference performance and sensitivity of the coated gas sensor are shown in Table 41. The response voltage values of the target gas methane and the interfering gas ethanol differed significantly from the comparative example, with a difference of 0.71V at the maximum response voltage, which could lead to false alarms. Compared to the uncoated sensor, the sensor with the prepared coating also produced a larger response voltage at 9-12 seconds of detection time, indicating that the coating does not affect the sensor's gas detection sensitivity. Large cracks appeared on the surface of the prepared coating, and scratches from sharp objects and clamping caused detachment and cracking.
[0342] Table 41. Anti-interference performance and adhesion / forming ability of the coated sensor in Example 40.
[0343] Table 42 shows the long-term stability test results of the gas sensor covered with the nanocomposite anti-interference material coating prepared in Examples 1-36. After 30 days of continuous testing, the average maximum response voltage of the gas methane and the interfering gas ethanol remained stable, indicating that the coating only plays a catalytic role against the interfering gas, can be reused, will not be consumed, and the surface coating will not fail.
[0344] Table 42 Long-term stability test of the coated sensor for detecting methane and ethanol.
[0345] The comprehensive performance evaluation of the anti-interference ability and adhesion ability of the gas sensors with anti-interference coating prepared in Examples 1-40 of this invention is shown in Table 43, among which Example 34 is the example with the best material ratio and the best preparation method.
[0346] The relationship between the operating temperature and anti-interference performance of gas sensors with anti-interference coatings: Under normal circumstances, the stable operating temperature of a gas sensor is approximately 350℃. Without a coating, the sensor's operating temperature rises by less than 10℃ when exposed to methane or ethanol. However, a gas sensor with an anti-interference coating experiences a temperature rise of up to 40℃ when exposed to methane or ethanol. This significant difference is due to the crucial role of the anti-interference coating. On the surface of the gas sensor, the anti-interference coating possesses unique catalytic properties: when interfering gases such as ethanol come into contact with the coating, the coating catalyzes the reaction, causing a violent chemical combustion reaction. This reaction releases a large amount of heat, which is rapidly transferred to the sensor's interior, disrupting its original thermal equilibrium and resulting in a significant increase in the sensor's operating temperature.
[0347] In the series of embodiments involved in this invention, a clear pattern emerges: the sensors in all qualified and above embodiments exhibit a significantly greater increase in operating temperature compared to the sensors in unqualified embodiments and the uncoated sensors. This phenomenon fully demonstrates that the anti-interference coating plays a crucial role in improving the anti-interference performance of gas sensors. Sensors in qualified and above embodiments can more effectively catalyze the chemical reaction of interfering gases, resulting in a more significant change in operating temperature when facing interfering gases. This allows for more accurate differentiation between target and interfering gases, significantly improving the sensor's anti-interference capability and detection accuracy. Uncoated sensors, lacking this catalytic effect, are significantly inferior in anti-interference performance. Sensors in unqualified embodiments have defects in coating formulation and preparation processes, leading to poor catalytic effect, insignificant operating temperature changes, and unsatisfactory anti-interference performance.
[0348] Sensitivity analysis of gas sensors with anti-interference coating: Analysis of the changes in response voltage of the detected gas at different detection times reveals that the coated sensor not only has strong anti-interference and adhesion capabilities, but also has no impact on the sensor's sensitivity. The response voltage changes of gas sensors with and without coating are basically the same, indicating that the anti-interference coating does not affect the sensitivity of the gas sensor.
[0349] In summary, the gas sensor covered with the anti-interference coating has strong anti-interference and adhesion capabilities while maintaining its original sensitivity. This indicates that the coating only acts as a catalyst for interfering gases, can be reused, will not be consumed, and the surface coating will not fail.
[0350] Table 43 Comprehensive Evaluation of Interference Resistance and Adhesion of Overlay Coated Sensors
Claims
1. An anti-interference coating for the surface of a gas sensor, characterized in that, The material comprises the following parts by weight: 5.5-10.5 parts of nano-silica, 3.5-5.6 parts of nano-titanium dioxide, 10-15.5 parts of nano-tin dioxide, 1-2 parts of palladium chloride substrate, and distilled water.
2. The anti-interference coating on the surface of a gas sensor according to claim 1, characterized in that, The material comprises the following parts by weight: 8.3-9.7 parts of nano-silica, 4.2-5.2 parts of nano-titanium dioxide, 10.8-13.2 parts of nano-tin dioxide, 1-2 parts of palladium chloride substrate, and distilled water.
3. The anti-interference coating on the surface of a gas sensor according to claim 2, characterized in that, The material comprises the following parts by weight: 9.1 parts nano-silica, 4.6 parts nano-titanium dioxide, 11.8 parts nano-tin dioxide, 1.5 parts palladium chloride substrate, and distilled water.
4. A method for preparing an anti-interference coating on the surface of a gas sensor as described in any one of claims 1-3, characterized in that, Includes the following steps: S1: Thoroughly mix and grind nano-tin dioxide, nano-silicon dioxide, and nano-titanium dioxide; S2: The material mixed with S1 is sintered at a temperature of 300℃-500℃ for 1-2 hours. S3: The sintered nanocomposite material of S2 is mixed with a chemical aqueous solution of palladium chloride substrate and a polar protic solvent, and then ground again; S4: The nanocomposite material after S3 mixing and grinding is dried to remove the solvent, forming the final gas sensor nanocomposite anti-interference material coating.
5. The method for preparing an anti-interference coating on the surface of a gas sensor according to claim 4, characterized in that, The tin dioxide in step S1 is tin dioxide prepared by chemical oxidation or calcination of metallic tin with a purity of 99.999%.
6. The method for preparing an anti-interference coating on the surface of a gas sensor according to claim 4, characterized in that, In step S2, the sintering temperature is 340℃-440℃ and the time is 2 hours. In step S4, the drying temperature is 60℃-100℃.
7. The method for preparing an anti-interference coating on the surface of a gas sensor according to claim 6, characterized in that, In step S2, the sintering temperature is 380℃ and the time is 2 hours.
8. The method for preparing an anti-interference coating on the surface of a gas sensor according to claim 6, characterized in that, The drying temperature in step S4 is 80°C.
9. The method for preparing an anti-interference coating on the surface of a gas sensor according to claim 4, characterized in that, In step S3, the palladium chloride substrate chemical aqueous solution is a 10% palladium chloride substrate chemical aqueous solution, and the polar protic solvent is water or ethanol.
Citation Information
Patent Citations
V2O5 nanoflower structure-based xylene gas sensor and preparation method thereof
CN114295689A
Oxidation catalyst on a substrate utilized for the purification of exhaust gases
US20060211569A1
Gas detecting method and apparatus
US5528225A